2020
DOI: 10.1021/acs.cgd.0c00801
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Control of Self-Assembled Three-Phase Au-BaTiO3–ZnO Hybrid Metamaterial for Tunable Optical Properties

Abstract: Microstructural control in metal-dielectric hybrid metamaterials presents enormous opportunities in tailoring the physical properties including the magnetic and optical properties. Here, we demonstrate a strong tunability achieved in the microstructure of self-assembled ordered three-phase Au-BaTiO 3 −ZnO hybrid metamaterial along with its optical properties, grown by a pulsed laser deposition method. Varying the growth temperature, deposition frequency, and template thickness evolves the microstructure by tun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Different from the typical “top‐down” techniques such as electron beam lithography (EBL), [ 20,21 ] focused ion beam (FIB), [ 22,23 ] and “bottom‐up” electrochemical templating methods, [ 24,25 ] the direct growth of self‐assembled oxide‐metal hybrid metamaterials in the vertically aligned nanocomposite (VAN) thin film form has been demonstrated as an alternative “bottom‐up” approach. [ 26–30 ] Interestingly, highly tunable optical properties such as localized surface plasmon resonance (LSPR) and hyperbolic dispersion shift in the UV–Vis–NIR wavelength region achieved by varying nanostructure aspect ratios, [ 31,32 ] pillar density, [ 32–34 ] and substrate selections [ 35,36 ] all present enormous potentials for these new class of hybrid thin films. Furthermore, by properly selecting the metal nanopillar phase and oxide or nitride matrix, other novel functionalities such as tunable ferroelectric, ferromagnetic, and magnetoelectric coupling and thermal stability can also be enabled.…”
Section: Introductionmentioning
confidence: 99%
“…Different from the typical “top‐down” techniques such as electron beam lithography (EBL), [ 20,21 ] focused ion beam (FIB), [ 22,23 ] and “bottom‐up” electrochemical templating methods, [ 24,25 ] the direct growth of self‐assembled oxide‐metal hybrid metamaterials in the vertically aligned nanocomposite (VAN) thin film form has been demonstrated as an alternative “bottom‐up” approach. [ 26–30 ] Interestingly, highly tunable optical properties such as localized surface plasmon resonance (LSPR) and hyperbolic dispersion shift in the UV–Vis–NIR wavelength region achieved by varying nanostructure aspect ratios, [ 31,32 ] pillar density, [ 32–34 ] and substrate selections [ 35,36 ] all present enormous potentials for these new class of hybrid thin films. Furthermore, by properly selecting the metal nanopillar phase and oxide or nitride matrix, other novel functionalities such as tunable ferroelectric, ferromagnetic, and magnetoelectric coupling and thermal stability can also be enabled.…”
Section: Introductionmentioning
confidence: 99%
“…[ 113 ] Therefore, due to the anisotropic nanostructure and lattice strain coupling at the pillar/matrix and film/substrate interfaces, the VAN hybrid thin films are expected to have enhanced SHG response compared with the pure NLO materials. [ 43,102,111 ] More interestingly, noncentrosymmetric and anisotropic nature has been demonstrated in the Au–TaN hybrid thin film with both phases of centrosymmetric crystal structures. [ 45 ] The comparison of the SHG intensity of TaN and Au–TaN films as a function of incident polarization angle fixed at 0° (P‐out) and 90° (S‐out) are shown in Figure a,b, respectively.…”
Section: Part V: Multifunctionality Achieved Using Van Platformsmentioning
confidence: 99%
“…It is noted that the HMM transition wavelengths show a noticeable blue-shift from 868 nm for the Au-BTO film to 669 nm for Au x Ag 1Àx -BTO film, indicating higher electron density as other study reported. [46,102]…”
Section: Au X Ag 1àx -Bto Van Systemmentioning
confidence: 99%
“…All of these examples have shown great potentials in achieving various artificial metamaterial designs possessing relatively good periodicity, large-scale surface coverage, epitaxial quality, atomic-sharp interface, as well as tunable functionalities. Table 1 summarizes the recent ceramic-based wire metamaterials (or VANs) grown by physical vapor deposition technique, and their reported functionalities [51][52][53][54][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74]. The ultimate goal is to realize an alternative method in fabricating functional heterostructures or metamaterials for applications including sensing, high-temperature plasmonics, nonlinear optics, ultrafast switching, as well as fundamental explorations, including tunable plasmonics or coupled multifunctionalities, using these highly anisotropic media.…”
Section: Nanostructure Fabricationmentioning
confidence: 99%